Real-world analysis of teclistamab in 123 RRMM patients from Germany - Riedhammer, Christine; Bassermann, Florian; Besemer, Britta; Bewarder, Moritz; Brunner, Franziska; Carpinteiro, Luiz Alexander Treiber Alves; Einsele, Hermann; Faltin, Josefine; Frenking, Jan; Gezer, Deniz; Goldman-Mazur, Sara; Hänel, Mathias; et al. (Leukemia, 2024)
Teclistamab, a B-cell maturation antigen (BCMA) × CD3 directed bispecific antibody, has shown high response rates and durable remissions in the MAJESTEC-1 trial in patients with relapsed and refractory multiple myeloma (RRMM). We retrospectively assessed efficacy and tolerability in 123 patients treated at 18 different German centers to determine whether outcome is comparable in the real-world setting. Most patients had triple-class (93%) or penta-drug (60%) refractory disease, 37% of patients had received BCMA-directed pretreatment including idecabtagene vicleucel (ide-cel) CAR-T cell therapy (21/123, 17.1%). With a follow-up of 5.5 months, we observed an overall response rate (ORR) of 59.3% and a median progression-free survival (PFS) of 8.7 months. In subgroup analyses, we found significantly lower ORR and median PFS in patients with extramedullary disease (37%/2.1 months), and/or an ISS of 3 (37%/1.3 months), and ide-cel pretreated patients (33%/1.8 months). Nonetheless, the duration of response in ide-cel pretreated patients was comparable to that of anti-BCMA naive patients. Infections and grade ≥3 cytopenias were the most frequent adverse events. In summary, we found that teclistamab exhibited a comparable efficacy and safety profile in the real-world setting as in the pivotal trial.